Trematode species of the order Aspidogastrida parasiting in turtle Pelodiscus sinensis (Wiegmann, 1834) in Vietnam - Doanh, Pham Ngoc (Academia Journal of Biology, 2006)
Upto now, there is few article about Aspidogastrid in Vietnam. This paper describes 3 species of the order Aspidogastrida Skrjabin et Guschanskaja, 1962 collected from turtles (Pelodiscus sinensis (Wiegmann, 1834)) in Vietnam. They are: Cotylapsis sinensis Faust et Tang, 1936, Lophotaspis orientalis Faust et Tang, 1936 and Lophotaspis interiora Ward et Hopkins, 1931. Among them, 2 species Cotylapsis sinensis and Lophotaspis interiora are recorded for the first time in Vietnam.